The Epidermolysis Bullosa Disease Activity and Scarring Index (EBDASI): grading disease severity and assessing responsiveness to clinical change in epidermolysis bullosa. (3rd October 2016) - Jain, S.V.; Harris, A.G.; Su, J.C.; Orchard, D.; Warren, L.J.; McManus, H.; Murrell, D.F.
Abstract: Background: The lack of validated outcome measures for epidermolysis bullosa (EB) presents major barriers to evaluating disease severity and comparing the efficacy of therapies. The Epidermolysis Bullosa Disease Activity and Scarring Index (EBDASI) was recently introduced as a valid and reliable instrument for EB; however, its interpretation for use in clinical practice and clinical trials is yet to be defined. Objective: To assess the interpretability of the EBDASI in classifying patients according to disease severity and clinical response. Methods: A total of 53 outpatients with EB at two interstate institutions were prospectively evaluated. At each visit, the principal dermatologist completed the EBDASI and global assessments of disease severity and change. Classifications for mild, moderate and severe disease using the EBDASI were determined using receiver operating characteristic curves. Minimal clinically important differences for the EBDASI activity subscale were calculated and compared with the standard error of measurement. Results: Total EBDASI score ranges of 0–42, 43–106 and 107–506 corresponded to mild, moderate and severe disease respectively. Reduction in EBDASI activity scores of greater than 9 indicated clinically significant improvement. An increase of 3 in the activity score indicated deterioration. Conclusion: The EBDASI is a responsive tool and may be useful in characterizing disease severity and response. The cut‐offs proposed in this study provide the first practical guide for interpreting the EBDASI, further supporting its use for longitudinal patient assessment and in clinical trials.